The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jaac.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Persistent, Limited, and Delayed Problematic Cannabis Use in Early Adulthood: Findings From a Longitudinal Study

Abstract: Objective To identify risk profiles associated with patterns of problematic cannabis use in early adulthood. Method Data came from 1,229 participants in the Great Smoky Mountains Study, a prospective 20-year cohort study from 1993–2015 that is representative of western North Carolina with yearly assessments conducted from ages 9 to 16, and assessments at ages 19, 21, 26, and 30. Patterns of problematic cannabis use (i.e., DSM-5 cannabis use disorder or daily use) in early adulthood included 1) non-problemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Longitudinal studies have distinguished delayed risk in late adolescence/emerging adulthood by histories of externalizing behaviors, child maltreatment, and being bullied by peers, whereas other patterns of use (e.g., limited use) have been characterized by family instability and anxiety disorders (134). However, a nonlongitudinal study of men with substance abuse reported nearly identical childhood and adolescent risk factors (135), while another longitudinal study (136) found similar factors to be predictive of adolescent and adult illicit drug use, with the addition of early cannabis use as a significant catalyst for both groups, thus complicating our ability to disentangle which factors may be more closely coupled with delayed vs. early risk.…”
Section: Putative Underpinnings Of Distinct Developmental Trajectoriesmentioning
confidence: 99%
“…Longitudinal studies have distinguished delayed risk in late adolescence/emerging adulthood by histories of externalizing behaviors, child maltreatment, and being bullied by peers, whereas other patterns of use (e.g., limited use) have been characterized by family instability and anxiety disorders (134). However, a nonlongitudinal study of men with substance abuse reported nearly identical childhood and adolescent risk factors (135), while another longitudinal study (136) found similar factors to be predictive of adolescent and adult illicit drug use, with the addition of early cannabis use as a significant catalyst for both groups, thus complicating our ability to disentangle which factors may be more closely coupled with delayed vs. early risk.…”
Section: Putative Underpinnings Of Distinct Developmental Trajectoriesmentioning
confidence: 99%
“…For substance use disorders, we focused on ages 25 and 30 years, when substance use is not widespread but associated with a poor long-term prognosis. 36,37…”
Section: Methodsmentioning
confidence: 99%
“…55 Psychological attributes [56][57][58] and mental health challenges are both associated with substance use in youth. 24,59 In the NDIT study, high stress levels, impulsivity, novelty seeking, and lower self-esteem were associated with daily cannabis use. These findings may pertain to the selfmedication hypothesis, which posits that people with mental health-related vulnerability use substances to alleviate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Potential risk factors investigated were selected as associated with cannabis use based on findings of earlier studies, 7,[22][23][24][25][26][27][28][29] as well as the availability of data on the variable in the NDIT study, and included 6 sociodemographic characteristics (i.e., age, sex, mother university educated, language spoken at home, born in Canada, lives with 1 parent only), 7 psychosocial indicators (i.e., depressive symptoms, 32 family stress, 33,34 other stress, 33,34 impulsivity, 35,36 novelty seeking, 37 self-esteem, 38 worry about weight 33 ), 7 lifestyle indicators (i.e., use of alcohol, tobacco products other than cigarettes, smoked cigarettes, 39 number of bouts of participation in moderate and vigorous physical activity [MVPA] in the past week, 40 participation in team sports, computer hours/week, TV hours/week), 3 indicators pertaining to smoking in the social environment (i.e., parent(s) smokes, sibling(s) smoke, friend(s) smoke), and other (i.e., BMI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation